Resilient Peri-Urban Agriculture as a Regional Ecosystem Service: Dynamics, Governance Gaps, and Planning for Sustainability - Munkombwe, Joshua; Siankwilimba, Enock; Leliana, Defin Helda (Perencanaan Wilayah dan Kota FT UB, 2025)
Peri-urban agriculture (PUA) provides vital ecosystem services to urban regions—from local food security and flood mitigation to biodiversity conservation and recreation—yet it is increasingly strained by urbanization pressures. This review synthesizes recent research on PUA’s multifaceted role as a regional ecosystem service and examines how rapid urban expansion is reshaping peri-urban landscapes. The synthesis highlights recurring patterns of agricultural land fragmentation, ecosystem service degradation, and socio-economic transformation in peri-urban zones under urban expansion, with notable contrasts between developed and developing regions. The review further identifies conditions under which PUA systems demonstrate resilience or decline, showing that the loss of peri-urban farmland can exacerbate urban vulnerabilities such as disaster risk and food insecurity. Persistent urban–rural governance gaps and spatial planning challenges emerge as central constraints, as peri-urban areas frequently fall between rural and urban jurisdictions, resulting in fragmented policies and institutional blind spots. Drawing on comparative evidence from multiple regional contexts, the review concludes with policy-relevant insights for strengthening peri-urban governance, safeguarding agricultural land, and enhancing the contribution of peri-urban agriculture to sustainable urban and regional development.